An Interdisciplinary Pain Rehabilitation Programme: Description and Evaluation of Outcomes - Bosy, Dan (University of Toronto Press Incorporated, 2010)
Purpose: The purpose of this archival report is to describe the essential elements of an intensive 8-week interdisciplinary pain rehabilitation programme (IPRP) with a cognitive–behavioural emphasis and the results that can be expected in treating patients with chronic pain conditions. Method: This report describes a private outpatient program providing treatment services to patients with long-term disabling pain arising from work- or accident-related musculoskeletal injuries. The cohort consists of 338 consecutive patients who completed the program over a 3-year period (patients discharged between January 1, 2005, and December 31, 2007). Results: Improvements in vocational status were noted in 75% of patients with chronic pain. Patients were also able to reduce their pain levels by approximately 16% and to reduce their levels of anxiety and depression by 13% and 17% respectively. At the same time, 61% of patients were able to reduce or eliminate their pain medications. Conclusions: Outcomes are consistent with evidence-based clinical practice guidelines for the management of chronic pain conditions. The published literature supports the efficacy of this interdisciplinary approach in highly disabled patients for whom effective treatment has been delayed. Early intervention in the subacute phase is recommended for prevention of long-term disability in patients with chronic pain.